Sequencing effects of concurrent strength and endurance training on selected measures of physical fitness in young male soccer players: A randomized matched-pairs trial - Blechschmied, R.; Hermse, M.; Gäbler, M.; Elferink-Gemser, M.; Hortobágyi, T.; Granacher, U. (Sports Medicine - Open, 2023)
Background Various physical fitness qualities such as muscle strength, speed and endurance are related to soccer performance. Accordingly, the combination of strength and endurance training (i.e., concurrent training [CT]) is an often-encountered training regimen in soccer. Less is known about the effects of CT sequencing on performance in young soccer players. The aim of this study was to assess the sequencing effects of strength and intermittent endurance training applied within the same training session (intrasession) on measures of physical fitness and soccer performance in young soccer players.